2015
DOI: 10.1021/jp510656d
|View full text |Cite
|
Sign up to set email alerts
|

Prototropic Exchange Governs T1 and T2 Relaxivities of a Potential MRI Contrast Agent Nanozeolite Gd−LTL with a High pH Responsiveness

Abstract: Aqueous suspensions of lanthanide exchanged zeolite LTL have been investigated by 1 H, 17 O NMR, and EPR relaxivity studies. Both the longitudinal and the transverse relaxivity of these Gd 3+ loaded materials are strongly pH dependent and therefore, they have great potential as pH responsive contrast agents. For example, LTL-nanocrystals loaded with 3.5 wt% Gd show a dramatic decrease in the longitudinal relaxivity from 32 to 7 s -1 mM -1 (7.5 T and 25 °C) when going from pH 4 to 9. 1 H and 17 O NMR show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 55 publications
3
24
0
Order By: Relevance
“…Here we observe a strong dependence of the relaxivity on the concentration of the encapsulated contrast agent (Figure 3a). Decreasing the amount of encapsulated contrast agent from the maximum concentration of 0.2 M to the minimum concentration of 4 × 10 −3 M Gadobutrol solution inside the nanocarriers led to an increase of the relaxivity from ≈22 to ≈40 s −1 mmol −1 L. As the relaxivity of a contrast agent is usually independent of its concentration, this trend is an intrinsic effect of the confinement in nanocapsules and was observed before for polyurea nanocapsules, [45] for nanozeolites [61] as well as for silica nanoparticles. [29,62] It can be attributed to a saturation effect.…”
Section: Relaxivity and Distribution Of Gadobutrol In The Nanocapsulessupporting
confidence: 55%
“…Here we observe a strong dependence of the relaxivity on the concentration of the encapsulated contrast agent (Figure 3a). Decreasing the amount of encapsulated contrast agent from the maximum concentration of 0.2 M to the minimum concentration of 4 × 10 −3 M Gadobutrol solution inside the nanocarriers led to an increase of the relaxivity from ≈22 to ≈40 s −1 mmol −1 L. As the relaxivity of a contrast agent is usually independent of its concentration, this trend is an intrinsic effect of the confinement in nanocapsules and was observed before for polyurea nanocapsules, [45] for nanozeolites [61] as well as for silica nanoparticles. [29,62] It can be attributed to a saturation effect.…”
Section: Relaxivity and Distribution Of Gadobutrol In The Nanocapsulessupporting
confidence: 55%
“…Our previous investigations on the relaxation mechanism revealed that above pH 7 the water structuring inside the zeolite is disrupted by ionization of the silanol groups, Gd III -bound water molecules, and decreased concentration of hydronium ions. 19 This effect is less pronounced in case of the PEGylated Gd-LTL, resulting in a slightly less decrease of r 2 ( Δr 2 = 22 s –1 mM –1 ) compared to that of the non-PEGylated analogue (Figure 4b).…”
Section: Resultsmentioning
confidence: 89%
“…19 For this system (Figure 1), six water molecules in first coordination sphere of Ln III in the large cages of LTL have been determined by the measurements of luminescence lifetimes of Eu III . 17 The relaxivities showed a steep decrease from 38 to 8 s –1 mM –1 for r 1 and from 98 to 50 s –1 mM –1 for r 2 , respectively, when moving from pH 4 to 9 (7 T and 25 °C).…”
Section: Introductionmentioning
confidence: 99%
“…The increased per-Gd 3+ relaxivity observed for each chelate incorporated into a NAC seems to derive entirely from second-sphere contributions enhanced by slowed molecular tumbling (long τ R ). We therefore speculate that the exchange of relaxed protons from the chelate's second-sphere across the aggregate interior and silica shell to the bulk solvent occurs primarily through proton exchange (22). Whole water exchange is probably only involved in the final exchange step at the SNP shell.…”
Section: Discussionmentioning
confidence: 94%
“…We therefore speculate that the exchange of relaxed protons from the chelate’s second-sphere across the aggregate interior and silica shell to the bulk solvent occurs primarily through proton exchange. (22) Whole water exchange is probably only involved in the final exchange step across the silica shell.…”
Section: Discussionmentioning
confidence: 99%